Basalt short fiber oriented reinforced rubber composite material and preparation method thereof

By surfactant treatment of basalt staple fibers and re-modification of sodium stearate solution, the problem of poor adhesion between basalt staple fibers and rubber is solved, and the performance and service life of the composite material are significantly improved.

CN119529335APending Publication Date: 2025-02-28QINGDAO UNIV OF SCI & TECH

Patent Information

Application Number
CN202411672636.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-21
Publication Date
2025-02-28

AI Technical Summary

Technical Problem

The poor adhesion of basalt staple fibers to rubber leads to limited product performance and service life.

Method used

Using a special surfactant treatment method, the BSF is modified again by pretreating basalt staple fibers with sodium stearate solution to improve its compatibility and adhesion with the rubber matrix.

Benefits of technology

It significantly improves the tensile strength, acron wear performance and rolling resistance of basalt staple fiber reinforced rubber composites, extending the service life of the product.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119529335A_ABST
    Figure CN119529335A_ABST
Patent Text Reader

Abstract

The invention discloses a preparation method of a basalt short fiber (BF) oriented reinforced rubber composite material. The method comprises the following steps: 1) pretreating BF; 2) proportionally weighing BF and other raw materials, and sequentially adding the BF and other raw materials into an internal mixer for mixing; and (3) after uniformly mixing, carrying out open milling and sheet discharging, and carrying out performance test after carrying out calendering orientation vulcanization on the obtained rubber material along the BF direction. The composite material comprises the following components in parts by mass: SCR5: 85; 15 parts of BR; 0.3 part of CTP (Cellulose Triphosphate); n234: 43; dZ: 1.8; bF: 3 is firstly treated; s: 1; and after the two-stage mixing, the rubber material is subjected to calendering orientation along the BF direction and is vulcanized along the orientation direction. The pre-treated BSF is treated by using a sodium stearate method, so that the physical and mechanical properties of the composite material are relatively good, the pre-treated BF after pretreatment is relatively high in lipophilicity and relatively good in compatibility with a rubber matrix, and the comprehensive performance of the modified BF after being matched with latex and the like is relatively high.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of polymer materials, and in particular to a basalt short fiber oriented reinforced rubber product. Background Art

[0002] Short fiber / rubber composite material (SFRC for short) is a new type of polymer material that has the rigidity of short fibers and the high elasticity of rubber, and gives its products a series of excellent properties such as high modulus, high hardness, tear resistance, puncture resistance, cutting resistance, low compression deformation, load fatigue resistance, low heat generation, anti-swelling and anti-creep.

[0003] Basalt short fiber (BSF / BF) has excellent mechanical properties and stability, high temperature resistance, good chemical resistance, easy processing and low cost, and has excellent low rolling resistance. Many domestic scholars have conducted in-depth research on basalt fiber. Wu Weili et al. used basalt short fiber to prepare BSF / silicone rubber composite materials, and its physical properties were improved. Wei et al. conducted in-depth research on the modified application of BSF, but there are not many studies on BSF to reduce rubber rolling resistance. Most of the research focuses on using solution-polymerized styrene-butadiene rubber to reduce rubber rolling resistance, the use of carbon black and white carbon black, and the research and design of natural rubber molecules using epoxy modification methods.

[0004] Due to the characteristics of BSF itself, the interface adhesion between BSF and rubber plastic matrix is ​​poor. It is necessary to select suitable coupling agents and adhesives and establish an ideal bonding system to pre-treat the surface of basalt fiber. In the rubber industry, the bonding between rubber and skeleton materials is very important, and the bonding level between them determines the performance and service life of the product.

[0005] CN201611099684.0 discloses a fiber / metal layer structure composite material and a preparation method thereof, and relates to the field of functional composite material manufacturing. The fiber / metal layer structure composite material is composed of fiber resin layers and metal layers alternately, wherein a rubber layer may be added; a repair agent microcapsule and a catalyst are added to the resin, and micron-level strength enhancing particles may also be added. The preparation method comprises impregnating the fiber with resin to form a fiber resin layer; surface treating the metal sheet to form a metal layer; alternately laying the fiber resin layer and the metal layer in the mold cavity; heating, pressurizing and curing the layer structure in the mold cavity. The present invention combines the advantages of fiber resin composite materials, metals and rubbers, and has strong designability; the functional composite materials designed with outstanding characteristics such as high specific strength, fatigue resistance, corrosion resistance, and high damping meet the urgent needs of aerospace, national defense, rail transportation, automobiles and other fields for new materials to a certain extent. CN201611165391.8 relates to the field of conductive rubber, and specifically to a high-performance conductive rubber composite material and a preparation method thereof. The high-performance conductive rubber composite material is composed of the following raw materials in parts by weight: 80-100 parts of methyl vinyl silicone rubber, 16-20 parts of basalt short fibers, 20-22 parts of silver-plated glass microsphere powder, 4-6 parts of carbon nanotubes, 0.8-1.2 parts of graphene, 1-4 parts of hydrogenated silicone oil, 1-2 parts of γ-aminopropyltriethoxysilane, and vinyltrimethoxysilane. 1-3 parts, 4-6 parts of zinc oxide, 2-3 parts of nano magnesium hydroxide, 0.5-1.5 parts of sodium stearate, 2-5 parts of vulcanizing agent, 2-4 parts of nano filler, 0.8-1.5 parts of anti-aging agent, and its preparation method mainly includes four steps: weighing, pretreatment, modification treatment, and mixing. The high-performance conductive rubber composite material of the present invention has excellent conductivity, and also has good mechanical strength, high temperature resistance, corrosion resistance and flame retardancy, excellent comprehensive performance, simple preparation method, and easy to realize industrial production. Shuaicheng G et al. experimentally studied three types of surface treatment, including epoxy resin impregnation, impregnation in nano silica suspension, and combined treatment of silane coupling agent and nano silica, to improve the high temperature resistance and durability of carbon fiber reinforced concrete (CTRC) and basalt fiber reinforced concrete (BTRC). The bending strength results show that the modification effect of nano silicon impregnation on the interface bonding of CTRC is greater than that of BTRC. KVB et al. found that chemical treatment of basalt fibers with functionalized nanomaterials resulted in BFRPs with a good stiffness-toughness balance, which in this paper included matrix functionalization, silane treatment, functionalized nanomaterial coating, and plasma polymerization. Qing W et al. first demonstrated the superiority of β-CD in strengthening the interface between BF and epoxide. MI et al. found that better performance was obtained when basalt fibers modified with a complex mixture of silanes were dispersed in a cement matrix.However, the common pretreatment method for basalt fiber is usually silane coupling agent, such as KH550 (3-aminopropyltriethoxysilane), KH560 (γ-(2,3-epoxypropyloxy)propyltrimethoxysilane) and Si69. In addition, the study on the effect of organic salt or silane coupling agent on the properties of pretreated basalt staple fiber and the interaction with BF surface groups is not mentioned in the prior art. Summary of the invention

[0006] In view of this, the present invention aims at the above problems and proposes a basalt short fiber oriented reinforced rubber product, which adopts a special surface active treatment method to obtain the best adhesive treatment method, so that the performance of the reinforced rubber composite material is greatly improved.

[0007] In order to achieve the above object, the present invention adopts the following technical solution: a method for preparing a basalt short fiber oriented reinforced rubber composite material, comprising the following steps:

[0008] (1) Pretreatment of basalt short fibers;

[0009] (2) weighing the pretreated short fibers and other raw materials in a certain proportion, and sequentially adding them into an internal mixer for mixing;

[0010] (3) After the mixing is uniform, the sheet is produced, and the obtained rubber material is calendered and oriented along the direction of the short fibers, vulcanized, and left for 6 hours for use. Finally, the performance test is carried out.

[0011] The raw material composition of the basalt short fiber oriented reinforced rubber composite material is calculated by weight:

[0012] 85 parts of NR (SCR5); 1 part of TMQ (RD); 15 parts of BR; 0.3 parts of anti-scorch agent CTP; 5 parts of white carbon black; 1 part of microcrystalline wax; 4 parts of ZnO; 0.5 parts of Si69; 2 parts of stearic acid SA; 2 parts of antioxidant 4020; 43 parts of carbon black N234; 1.8 DZ; 3 parts of pre-treated basalt staple fibers; 1 part of S.

[0013] Preferably, the pretreatment method of the basalt staple fibers comprises the following steps:

[0014] (1) First, dissolve an appropriate amount of ethanol in a small amount of water, then add appropriate amounts of different coupling agents KH550, KH560 and Si69, stir until the coupling agent is fully dissolved, and then add appropriate amounts of water to make the concentrations of ethanol and coupling agent reach 1.5% respectively.

[0015] (2) The BSF treated with KH550 was immersed in the prepared 1.5wt% coupling agent solution for 1 hour. During the immersion process, the stirrer speed was increased for dispersion for 1 hour. After being taken out, it was placed in a drying oven at 80°C for 4 hours to accelerate the reaction between the coupling agent and the chemical components on the surface of the BSF, thereby obtaining the pretreated basalt fiber.

[0016] Furthermore, the pretreatment method of the basalt staple fibers specifically comprises the following steps:

[0017] (1) At 60°C, 1.5 g of coupling agent was added to 62 ml of anhydrous ethanol and 49 ml of deionized water and stirred for 10 minutes for hydrolysis. The stirring speed was 200 r / min, and 111 ml of 1.5 wt% (total mass 100 g) coupling agent solution was prepared.

[0018] (2) The original KH550 treated 3phr / 4phr / 5phr chopped basalt fibers were cleaned with deionized water and placed in a beaker, and then immersed in 40ml / 54ml / 67ml of 1.5% (1.5wt%) coupling agent (KH550 or KH560 or Si69) solution containing ethanol, respectively, and stirred at a speed of 750r / min and a temperature of 60°C for 1h using a high-speed rotary machine, and then placed in an electric blower dryer for drying at 80°C for 4h.

[0019] Furthermore, the pretreatment method of the basalt staple fibers also includes a sodium stearate solution pretreatment method, the steps of which are:

[0020] (1) Add appropriate amount of C 17 H 35 COONa powder was placed in a solution with a quantitative mass fraction ratio of anhydrous ethanol: water = 1:1, and stirred until the coupling agent was fully dissolved.

[0021] (2) Soak an appropriate amount of pre-treated BSF in the above 1.5 wt% C 17 H 35 The solution of COONa was heated with stirring at a stirring speed of 1 h, and then taken out and placed in a drying oven at 80°C for 4 h to obtain pretreated basalt fibers.

[0022] Preferably, the sodium stearate solution pretreatment method specifically comprises the following steps:

[0023] (1) 15 g C 17 H 35 COONa powder was placed into 985 g of a solution with a mass fraction ratio of anhydrous ethanol to water = 1:1, and stirred for 10 minutes to promote hydrolysis at 60°C and a stirrer speed of 200 r / min.

[0024] (2) 108 g of pre-treated BSF (18 parts) was soaked in 240 ml of 1.5 wt% C 17 H 35 In the COONa solution, the constant temperature of the water bath is 60°C, and the stirrer speed is 750r / min for stirring and heating for 1h.

[0025] Preferably, the internal mixer mixing process in step (2) of the method for preparing the basalt short fiber oriented reinforced rubber composite material is:

[0026] 1) Mixing in one stage: lift the top bolt, put the raw rubber (85 parts NR, 15 parts BR) cut into small pieces into the internal mixer from the feeding port, close the top bolt, adjust the rotor speed to 70r / min, and mix for 30s;

[0027] Lift the top plug, add 5 parts of white carbon black, 21.5 parts of carbon black N234, 0.5 parts of Si 69, 3 parts / 4 parts / 5 parts of BSF (orthogonal test combination), close the top plug, mix for 120 seconds, and the rotor speed is 70r / min;

[0028] Lift the top plug, add 4 parts of zinc oxide, 2 parts of stearic acid SA, 1 part of microcrystalline wax, 21.5 parts of carbon black, 1 part of antioxidant RD, and 2 parts of 4020, close the top plug, adjust the rotor speed to 40r / min, mix for 4min30s, and discharge the glue;

[0029] 2) Second stage mixing:

[0030] The masterbatch obtained in step 1) was added with 1 part of sulfur, 1.8 phr DZ and 0.3 phr CTP; mixed for 60 seconds and discharged.

[0031] Preferably, in the calendering process of the mixing mill, the roller temperature is 40-50°C, the roller spacing of the mixing mill is adjusted to 1mm, and the mixing mill is rolled over 5 times along the calendering direction; then the roller spacing is adjusted to 3mm, and the mixing mill is rolled over 5 times along the calendering direction to obtain a basalt short fiber composite material oriented along the calendering direction.

[0032] Preferably, the basalt fiber pre-treatment method is KH550 pre-treatment. In the present invention, KH550 pre-treatment BF is equivalent to the commercially available BF pre-treated with KH550 solution in the prior art, and is named as such to distinguish it from the re-pretreatment in the present invention.

[0033] Furthermore, the pretreatment method is a combination of one or more of KH560, Si69, and sodium stearate solution treatment methods, especially sodium stearate solution treatment.

[0034] Preferably, the pretreatment method is to treat the pre-treated BSF in combination with a sodium stearate / KH560 solution and latex.

[0035] Furthermore, the pretreatment method is to synergistically treat the pre-treated BSF with sodium stearate / KH560 solution, latex and carbon black.

[0036] Preferably, the method of co-processing BSF with sodium stearate solution, latex and carbon black comprises the following steps:

[0037] 1) First, the natural rubber latex was subjected to a wall-breaking treatment, and 850 g of natural rubber latex (60%) solution was stirred in a high-speed stirrer at 1800 r / min for 8 min;

[0038] 2) C 17 H 35 COONa powder was placed in anhydrous ethanol: water = 1:1 solution and stirred for 10 minutes to promote hydrolysis at 80°C and 200 r / min stirring speed;

[0039] 108 g of pre-treated BSF (18 parts) was soaked in 240 ml of 1.5 wt% C 17 H 35 The COONa solution was heated in a constant temperature water bath at 60°C for 1 h and stirred at 750 r / min for 1 h.

[0040] Finally, the BSF modified by sodium stearate solution was dried in an electric heated air drier at 80 °C for 4 h to obtain modified BSF;

[0041] 3) Take out 3 parts of BSF after drying, add BSF into the treated natural rubber latex, and stir at 1800r / min for 1min at room temperature;

[0042] 4) Weigh 258g of carbon black (N234) into a beaker, then pour in 800g of deionized water, and stir the carbon black aqueous solution in a stirrer at a stirring speed of 750r / min for 5min to fully dissolve the carbon black;

[0043] 5) Then pour the latex into the carbon black aqueous solution (stirring while pouring), the stirring speed is 750r / min, the stirring time is 1min, and after completion, pour it into a glass dish, dry it in an oven for 6h, pour it into a large tray, lay it flat and dry it, cut it into small pieces, and prepare it into NR / BSF masterbatch;

[0044] Preferably, the mixing step after the method of pre-treating BSF with sodium stearate / KH560 solution, latex and carbon black is the same as the internal mixer mixing process in step (2) of the method for preparing basalt short fiber oriented reinforced rubber composite materials, the difference being that 85 parts of NR in the raw rubber cut into small pieces are replaced with NR / BSF masterbatch, and pre-treated BSF is not added separately.

[0045] Preferably, the short fiber reinforced rubber material after the rubber material is calendered on the open mixing mill is placed in a split-flow guided short fiber directional orientation die head for extrusion to obtain the short fiber directional orientation extruded rubber material.

[0046] Preferably, the extruder head structural parameters are: the diameter of the middle flow channel section is 48 mm, the length of the middle flow channel section is 0 mm, the barrel temperature is 80 degrees, and the extruder screw speed is 35 r / min. The extruded rubber material is cooled for 8 hours before vulcanization test.

[0047] The technical solution of the present invention has at least the following advantages and beneficial effects:

[0048] 1. The content of C element in the sodium stearate solution of the present invention is increased by 18.7% after further modification; the infrared spectrum test results show that the methyl group (-CH 3 ) and other groups were grafted into BF. Under the same re-modification conditions: the tensile strength of BF rubber composites treated with sodium stearate solution was increased by 3.4% compared with γ-(2,3-epoxypropoxy)propyltrimethoxysilane (KH560); the wear performance of Akron was increased by 10.9%. The contact angles of BF re-modified with sodium stearate solution / KH560 and water reached 127.0° and 121.1° respectively, and the lipophilicity of BSF was significantly improved.

[0049] 2. The present invention proposes an optimal method for re-modifying BSF with adhesives and explores the mechanism of re-modifying BSF; the experimental results show that the composite material of BSF treated with sodium stearate solution (KH550 has been pre-treated) has the best performance. Under the same conditions, the tensile strength of the rubber composite material reinforced with BSF re-modified with sodium stearate solution is 3.4% higher than that of KH560 re-modified, and the Akron wear performance is improved by 10.9%.

[0050] 3. Compared with the method of only treating with KH550, the BSF of the present invention is better in bonding with the rubber matrix by co-treatment with KH550 and then with KH560. The tensile strength of the BSF reinforced rubber composite material modified with KH560 can be increased by 6.1%, and the Akron wear performance can be increased by 33.1%. The contact angles of BSF treated with sodium stearate solution / KH560 with water are 127.0° and 121.1°, respectively.

[0051] 4. The BSF rubber composite material under the wet process of the present invention can more effectively enhance the physical and mechanical properties of the composite material and improve the rolling resistance than the dry process. The lipophilic groups and hydrophilic groups attached to the surface of BSF in the solution can combine with the lipophilic groups and hydrophilic groups in the natural latex to further enhance the adhesion between the natural rubber chain and BSF. In the radial direction, the tensile strength of the wet mixed rubber 8# (latex / carbon black / sodium stearate treated BSF) is 6.2% higher than that of the 7# rubber (dry process / BSF9 / sodium stearate) after extrusion, and the DIN wear performance is improved by 6.3%. The addition of DZ and CTP in the vulcanization system can prevent the rubber from scorching and vulcanization in the internal mixing, vulcanization and extrusion process. BRIEF DESCRIPTION OF THE DRAWINGS

[0052] Figure 1 The present invention is a flow chart of the preparation method of the basalt short fiber oriented reinforced rubber composite material;

[0053] The label 1: NR, BR; 2: white carbon black, carbon black N234, Si69, pre-treated basalt short fiber; 3: ZnO, SA, microcrystalline wax, carbon black, RD, 4020; 4: S, DZ, CTP; 4: mixed rubber: 5: vulcanized sample:

[0054] Figure 2 This is a diagram of the Akron abrasion S test and V' test specimen of the present invention;

[0055] The left side is S test along the calendering direction, the right side is V' test along the perpendicular direction of the calendering direction, and BF is oriented along the calendering direction.

[0056] Figure 3 This is an electron microscope image (60X) of the tensile test specimen of the present invention;

[0057] FIG4 is a diagram showing contact angles of BSF and water in different composite materials of the present invention;

[0058] Among them, (a) 6BSF3 phr untreated (99.8°); (b) KH560 3BSF4 phr (115.3°); (c) ethanol BSF9KH560 (121.1°); (d) 6BSF4 phr KH550 (94.5°); (e) C 17 H 35COONa (127.0°); (f) KH5503BSF5phr (110.9°); (g) BSF9 untreated (104.1°); (h) 3BSF3phr Si69 (113.2°); (i) 9BSF3phr KH550 (117.5°); (j) KH560-6BSF3phr (113.6°); (k) BSF3 untreated (87.5°); (l) Si69-6BSF5phr (107.4°); (m) Si69-9BSF4phr (118.3°);

[0059] FIG5 is a graph showing contact angles of different adhesives and BSF according to the present invention;

[0060] (a)C 17 H 35 COONa; (b) KH560; (c) KH550; (d) Si69; (e) H 2 O

[0061] FIG6 is an XPS broad spectrum of BSF in different composite materials of the present invention;

[0062] (a) is C 17 H 35 BSF after COONa treatment; (b) BSF after ethanol BSF9 KH560 treatment;

[0063] FIG7 is an energy spectrum diagram of KH560 modified basalt short fibers before and after the present invention;

[0064] (a1) Magnified image of the surface of basalt fiber after modification; (b1) Magnified image of the surface of basalt fiber before modification; (a2) Energy spectrum of basalt fiber after modification; (b2) Energy spectrum of basalt fiber before modification;

[0065] FIG8 is a comparison diagram of the surface tension of the wetting agent before and after modification of the present invention;

[0066] (a)C 17 H 35 COONa; (b) KH560; (c) KH550; (d) Si69; (e) H 2 O;

[0067] FIG9 is a FTIR spectrum of BSF in different composite materials of the present invention;

[0068] For the convenience of display, there are two spectra (a) and (b), both of which are FTIR spectra of powders after BF treatment with different adhesives in orthogonal test groups 1-13 of the present invention. DETAILED DESCRIPTION

[0069] The present invention is described below in conjunction with the accompanying drawings and specific embodiments.

[0070] To make the purpose, technical solution and advantages of the embodiments of the present invention clearer, the technical solution in the embodiments of the present invention will be described clearly and completely in conjunction with the accompanying drawings. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them.

[0071] Therefore, the following detailed description of the embodiments of the present invention is not intended to limit the scope of the invention claimed for protection, but merely represents some embodiments of the present invention. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0072] It should be noted that similar reference numerals and letters denote similar items in the following drawings, and therefore, once an item is defined in one drawing, further definition and explanation thereof is not required in subsequent drawings.

[0073] [Raw materials]:

[0074] Table 1 Main properties of main raw materials

[0075]

[0076] Table 2 Experimental formula table Unit / part

[0077]

[0078] In Table 2: Basalt fiber is short fiber treated by adding KH550 in the drawing process.

[0079] According to the experimental parameter conditions specified in Table 3, orthogonal experiments of BSF with different lengths / different numbers / different coupling agent treatments were carried out. After rolling on the mixing mill, relevant vulcanization experiments and physical and mechanical properties tests were carried out to obtain the optimal BSF material parameters.

[0080] Table 2 Orthogonal experiment of short fiber types and fractions

[0081]

[0082] In the table: R: fiber length; S: fiber number; T: coupling agent type. In the table: R, S, T, etc. have the same meanings as in Table 1.

[0083] Note: The basalt fibers in this experiment are basalt fibers that have been treated with KH550 during the drawing process. The fiber lengths are 3mm, 6mm, and 9mm, the fiber numbers are 3, 4, and 5, and the coupling agent types are KH550 / KH560 / Si69.

[0084] [Main experimental equipment and instruments]:

[0085] Open mixing mill, X(S)K-160, Shanghai Rubber Machinery Factory; internal mixer, X(S)M-1.7L, Qingdao Yilang Rubber Equipment Co., Ltd.; rotorless vulcanizer, MM4130C, Beijing Huanfeng Chemical Machinery Experimental Factory; flat plate vulcanizer, QLB-400X400X2, Qingdao Yilang Rubber Equipment Co., Ltd.; abrasion testing machine, GT-2012-D, Gaotie Technology Co., Ltd.; scanning electron microscope JSM-6700, Japan Electronics Corporation; universal tensile testing machine, 3366, Instron; KRüSS contact angle tester, KRUSS, KRUSS Scientific Instruments (Shanghai) Co., Ltd., Germany; infrared spectrometer, spectrum10OFT-IRspectrometer, made in the UK.

[0086] [Composite material performance testing process]:

[0087] (1) Physical and mechanical properties, SEM test

[0088] The vulcanization test conditions were determined based on the vulcanization characteristics measured by the MM4130C rotorless vulcanizer. The mold and sample used during vulcanization are shown in Figure 4(a) and Figure 4(b):

[0089] Due to the radial orientation of the short fibers, the vulcanized rubber has anisotropic properties. In order to characterize the anisotropy of the rubber compound and compare and analyze the influence of the short fiber orientation direction on the performance of the vulcanized rubber, performance test samples were prepared on a GT-7016-AB pneumatic automatic slicer along different orientation directions of the short fibers, as shown in Figure 4. The upper left corner of Figure 4 (a) is the horizontal direction S test sample; the lower right corner is the vertical direction V' test sample; the data disclosed in the embodiment of the present invention is the V' test, that is, the extrusion direction of the split-flow guided short fiber directional orientation die head, that is, the radial direction.

[0090] V' test method: Cut the rubber into strips along the vertical direction of the axial direction, a total of 24g, and place them along the lower right direction of the mold as shown in Figure 8(b), which is the radial direction. From Figure 4(b), it can be seen that the rubber is cut into strips along the Y direction, with a thickness of 2-4mm in the X direction, and the direction is perpendicular to the mold plane. The length of the film in the Y direction is not greater than the length of the vulcanization mold, and the thickness in the Z direction is determined according to the thickness of the extruded rubber, that is, the comprehensive physical and mechanical properties of the rubber in this direction can be measured.

[0091] The test was carried out on a UT-2060 tensile testing machine and a GT-2012-D abrasion testing machine, and the vulcanization conditions were 150°C / 10MPa×1.3T 90 . Abrasion standard: DIN53516 GB 9867, physical and mechanical properties test standard: GB527-533-65.

[0092] Firstly, the extruded rubber compound was pretreated as a test sample, and then the orientation degree of the short fibers was observed through photos using a JSM-6700F scanning electron microscope to obtain a SEM image.

[0093] (2) Akron wear test process

[0094] Test standard: GB / T 1689-2014 "Determination of wear resistance of vulcanized rubber (using Akron abrasion machine)".

[0095] As shown in Figure 4(c), the effects of different BSF radial orientation degrees on the properties of the rubber compound are compared. When Akron abrasion is performed, samples are cut along the radial direction and the extrusion direction of the rubber compound when it is milled on the mixing mill, respectively, for V" test and S test. The data disclosed in the embodiments of the present invention are oriented S tests, i.e., the extrusion direction of the mixing mill, i.e., the calendering direction.

[0096] (3) Infrared spectrum analysis of modified BF

[0097] The surface chemical composition of the modified BF was characterized by a Nicolet 380 Fourier transform infrared spectrometer. Then the surface chemical composition was tested by infrared spectrometer with a resolution of 2 cm -1 , scanning mode is 32 times, recording wavelength range is 4000~400cm -1 ), and perform 13-point smoothing on the collected data.

[0098] (4) Contact angle measurement after modified BF

[0099] Maintain a certain pressure and time on the tablet press, grind the modified BF into powder, and then use the tablet press to press it into a 10mm diameter round tablet with a smooth surface. Use a contact angle meter to measure the contact angle of distilled water droplets on it. Two experimental methods are adopted:

[0100] 1) The contact angle between BSF tablets and distilled water was measured using a video contact angle meter.

[0101] The contact angle was measured after the BSF powder in the orthogonal experiment of BSF optimal length / number of parts / coupling agent was pressed into tablets.

[0102] 2) Water, KH560, KH550, Si69, and sodium stearate solution (at 60°C) were dropped onto the BF powder disc that had been pre-treated with KH550 during the wire drawing process, and the contact angle was measured.

[0103] (5) Adhesive surface tension analysis

[0104] In the experiment, a video contact angle tester was used to test the surface tension of different adhesives using the hanging drop method.

[0105] (6) XPS analysis

[0106] The BSF without coupling agent treatment and the 17 H 35 XPS analysis of COONa solution, KH550, KH560 and Si69 treated monolithic BSF, experimental conditions:

[0107] A monochromator was used, A1 anode target was selected, X-ray beam was 9μm-15mm, energy resolution was 0.5ev, sensitivity was 3M CPS, angle was 45°. The vacuum degree of the analysis chamber was 6.7×10Pa, and the carbon standard was 284.8eV.

[0108] Sputtering conditions: Scanning Ar ion gun, area 1×1mm 2 , the sputtering rate is 14nm / min, the energy is 2.0KV, and the emission current is 20mA. The standard sample is thermally oxidized SiO 2 / Si.

[0109] [Preprocessing method]:

[0110] As preferred embodiments of the present invention, embodiments 1-9, embodiment 12: The pretreatment method of BSF treated with KH550, KH560, and Si69 solutions is:

[0111] (1) First, dissolve an appropriate amount of ethanol in a small amount of water, then add appropriate amounts of different coupling agents KH550, KH560 and Si69, stir until the coupling agent is fully dissolved, and then add appropriate amounts of water to make the concentrations of ethanol and coupling agent reach 1.5% respectively.

[0112] Take 18 parts of BSF as an example: first, dry 108g BSF (18 parts) in a vacuum drying oven at 80°C for 12h, then weigh 240ml of 1.5wt% coupling agent (KH550, KH560, Si69) solution, the solvent is a solution with a mass fraction of anhydrous ethanol: water = 1:1.

[0113] That is, at 60° C., 1.5 g of coupling agent was added to 62 ml of anhydrous ethanol and 49 ml of deionized water and stirred for 10 minutes for hydrolysis. The stirring speed was 200 r / min, and 111 ml of 1.5 wt% (total mass 100 g) coupling agent solution was prepared.

[0114] (2) The BSF pretreated with KH550 was immersed in the prepared 1.5 wt% coupling agent solution for 1 hour (the rotation speed was increased and dispersed for 1 hour), and then placed in a drying oven at 80°C for 4 hours to accelerate the reaction between the coupling agent and the chemical components on the surface of the BSF.

[0115] The specific method is: the original pre-treated (KH550 pre-treatment) 3phr / 4phr / 5phr short-cut basalt fiber is cleaned with deionized water and placed in a beaker, and then immersed in 40ml / 54ml / 67ml of 1.5% (1.5wt%) coupling agent (KH550 or KH560 or Si69) solution containing ethanol, and stirred at a speed of 750r / min and a temperature of 60°C for 1h with a high-speed rotary machine, and then placed in an electric blower dryer for drying at 80°C for 4h, where h represents hours.

[0116] Example 10: EDS test was performed using 6 mm BF, a total of 3 phr, without KH560 treatment.

[0117] Example 11: 3 portions of BF9mm, treated with KH560, without adding ethanol.

[0118] Implementation process of Example 11: The original pretreated 3phr short-cut basalt fiber 9mm was cleaned with deionized water and placed in a beaker, immersed in 40ml of 1.5% coupling agent KH560 solution, stirred at 750r / min at 60 degrees for 1h using a high-speed rotary machine, and then placed in an oven at 80°C for 4h to obtain a re-treated BSF.

[0119] Example 12: 3 portions of BF9mm, treated with KH560, and added with ethanol.

[0120] Example 13: 3 parts of BF9mm, plus sodium stearate (C 17 H 35 COONa), adding ethanol, and the preparation method of the pretreated basalt fiber is as follows:

[0121] The original pre-treated (KH550 treated) 3phr BF was cleaned with deionized water and placed in a beaker and immersed in 40ml of 1.5% C 17 H 35 COONa solution. The other experimental processes are the same as in Example 11. The following is the preparation process of the BSF reinforced rubber composite material in the experimental process, such as Figure 1 As shown:

[0122] The original pre-treated (KH550 treated) 3phr BF was cleaned with deionized water and placed in a beaker and immersed in 40ml of 1.5% C 17 H 35 COONa solution. The other experimental processes are the same as in Example 11. The following is the preparation process of the BSF reinforced rubber composite material in the experimental process, such as Figure 1 As shown:

[0123] [Mixing process]:

[0124] (1) Weigh the raw materials in proportion and add them into an internal mixer in sequence for mixing;

[0125] 1) One-stage mixing: lift the top plug, put the raw rubber (85 parts NR, 15 parts BR) cut into small pieces into the internal mixer from the feeding port, close the top plug, adjust the rotor speed to 70r / min, and mix for 30s; lift the top plug, add 5 parts of white carbon black, 21.5 parts of carbon black N234, 0.5 parts of Si 69, 3 parts / 4 parts / 5 parts of BSF (orthogonal test combination), close the top plug, mix for 120s, and the rotor speed is 70r / min; lift the top plug, add 4 parts of zinc oxide, 2 parts of stearic acid SA, 1 part of microcrystalline wax, 21.5 parts of carbon black, 1 part of antioxidant RD, and 2 parts of 4020, close the top plug, adjust the rotor speed to 40r / min, mix for 4min30s, and discharge the rubber;

[0126] 2) Second stage mixing:

[0127] The masterbatch obtained in step 1) was added with 1 part of sulfur, 1.8 phr DZ and 0.3 phr CTP; mixed for 60 seconds and discharged.

[0128] (2) After the mixing is uniform, the sheet is produced, and the obtained rubber compound is calendered and oriented along the direction of the short fibers. After vulcanization, the performance test is finally carried out, and the rubber compound is parked for 6 hours for standby, which is conducive to the uniformity and stability of the rubber compound performance and the elimination of internal stress. The rolling mill calendering process: the roller temperature is 40-50℃, the roller distance of the rolling mill is adjusted to 1mm, and the rolling is passed through the roller 5 times along the rolling direction of the rolling mill; then the roller distance is adjusted to 3mm, and the sheet is passed through the roller 5 times along the calendering direction to obtain a basalt short fiber composite material oriented along the calendering direction.

[0129] After calendering the rubber material, the rubber material along the calendering direction. After vulcanization, the performance test was carried out, and the test results were subjected to range analysis to obtain the best basalt fiber length / number / coupling agent combination with the best performance. After the orthogonal experimental results of Examples 1-9 in Table 4 were subjected to range analysis, the best combination was obtained as the optimal level combination of fiber length 9mm, fiber number 3phr, and coupling agent KH560.

[0130] [Result Analysis]:

[0131] Table 4 Orthogonal experiment results

[0132]

[0133] In Table 4: 1 , —300% tensile stress, MPa; σ 2 —Tensile strength, MPa; τ t —Tear strength, KN / m; ε t—Elongation at break, %; ΔV'—Akron wear volume, mm 3 ;

[0134] From the analysis of Table 4, it can be seen that the 300% modulus stress and tensile strength decrease first and then increase with the increase of fiber length (3mm-9mm), and with the coupling agent (Si69, KH550, KH560), increase with the increase of fiber content, and decrease with the coupling agent (Si69, KH550, KH560), and decrease with the increase of fiber content (3phr-5phr).

[0135] The elongation at break increases first and then decreases with the increase of fiber length (3mm-9mm) and fiber content (3phr-5phr), and the order of coupling agents (Si69, KH550, KH560). The tear strength decreases first and then increases with the increase of fiber length (3mm-9mm) and fiber content (3phr-5phr), and increases with coupling agents (Si69, KH550, KH560). Akron abrasion increases first and then decreases with the increase of fiber length (3mm-9mm) and fiber content (3phr-5phr), and the order of coupling agents (Si69, KH550, KH560) increases first and then decreases. From the perspective of the order of importance of various factors on various performance indicators, Akron abrasion, tensile strength, and tear strength are the main performance indicators, and the optimal level combination is determined in order as fiber length 9mm, fiber content 3phr, and coupling agent KH560.

[0136] Figure 3 This is the tensile electron microscope picture of the vulcanized sample of the 4th group (6mmBSF, KH560 treatment, ethanol addition, a total of 3 parts). From the picture, it can be seen that most of the short fibers are broken, proving that the bonding surface between the BSF after KH560 coarse particles and the rubber matrix is ​​better, and the tensile properties are significantly improved.

[0137] The results of the 4th and 10th groups of experiments show that the tensile strength of BSF treated with KH560 is 6.1% higher than that of BSF treated with KH550 during the wire drawing process alone, and the Akron wear performance is 33.1% higher. Adding ethanol as a solvent can promote the dissolution of organic substances such as coupling agents, so that the coupling agents can react better with BSF. The results of experiments 11 and 12 show that the comprehensive performance of the composite material with ethanol is higher than that without ethanol. The tensile strength of the rubber treated with sodium stearate along the calendering direction is 3.4% higher than that of BF9 treated with KH560 (with ethanol), and the Akron wear performance is improved by 10.9%.

[0138] Table 5 Contact angles of BF and water in different composite materials

[0139]

[0140] Table 6 Contact angles of BF and water in different composite materials (continued)

[0141]

[0142] As can be seen from Figure 4 and Table 5, with the increase of silane coupling agent KH560 in BF6, the instantaneous contact angle of BF powder tablets with water increases compared to BF6 without KH560, indicating that the surface property of BF6 changes from hydrophilic to hydrophobic; similarly, the contact angle of BF9 (after ethanol KH560 treatment) is 17° larger than that of BF9 (before treatment), indicating that the hydrophobicity of BF9 powder is significantly enhanced after re-modification.

[0143] As can be seen from Figure 4, Table 5, and Table 6, the contact angle between sodium stearate and water is the highest, which is 127.0°; followed by ethanol BF9, which is 121.1°, indicating that both have good lipophilicity. Since the concentration of the same coupling agent is consistent, the ninth level contact angle is consistent with ethanol BF9. Under the same short fiber length conditions, when the binder is added, the contact angle with water is significantly increased compared to the BF powder that is modified again without adding the binder, indicating that the surface lipophilicity of BF is significantly increased after adding the binder, and the surface pretreatment effect of BF is significantly improved.

[0144] Table 7 Contact angle of adhesive and BF

[0145]

[0146] From the analysis of Figure 5 and Table 7, it can be seen that in the process of measuring the contact angle between BF powder and adhesive after adding KH550 during the wire drawing process, the contact angle is significantly different when it contacts the flake powder and the immersion time. Compared with the traditional BF without any treatment, the BF powder has the characteristics of lipophilicity.

[0147] KH560 and other products have a smaller wetting angle, especially C 17 H 35COONa, because of its oiliness. The wetting angle refers to the contact angle between the droplet and the sample when it is stable. Since the contact angle changes too quickly, it cannot be proved that the wetting angle is this value for KH550, Si69, water, etc. The wetting angle is related to the interface between the two phases. It can only describe the instantaneous contact angle of various treatment agents when they come into contact with flaky powders, and judge the hydrophilicity and lipophilicity of the material at the same time as the immersion time. The surface roughness of the circular sample and the uniformity between the BF powders are also related to the immersion time. Therefore, there is still a certain error in the measurement. The contact angle of the sodium stearate solution is small when it first enters, and it has been tending to be stable (immersion time 47s), which is a manifestation of surface lipophilicity. Similarly, the initial contact angle between water and BF powder is large, which is caused by the lipophilicity of the BF powder surface, but the immersion time is short. Analysis shows that it is caused by the large gap between the BF powder particles in the middle. The immersion time of KH550 and Si69 is short, and the contact angle is small. However, after multiple tests, it was found that the immersion time is short, especially for Si69. The wetting angle belongs to the case with large errors. Comprehensive consideration, KH560 and sodium stearate have the best wettability. [Analysis of XPS test results of different samples]

[0148] Table 8 Interface element composition of BF in different composite materials (%)

[0149]

[0150] Table 9 Interface element composition of BF in different composite materials (%) (continued)

[0151]

[0152] From the analysis of Table 8 and Table 9, it can be seen that BSF contains SiO 2 At the same time, BSF absorbs moisture in the air and partially hydrolyzes to form Si-OH. As can be seen from Figure 6, the peaks of Si and S appear at 101.5ev and 151.31ev respectively. The peak at 101.5ev is mainly affected by the Si-OH bond formed by the elements in the crystal itself and the elements on the surface and the adsorbed water; the peak at 151.31ev is mainly the S element attached to the surface of BSF, which is due to the fact that Si69[molecular formula is (H 5 C 2 O) 3 Si(CH 2 ) 3 S 4 (CH 2 ) 3 Si(OC 2 H 5 ) 3] is present and attached to the surface layer of BF, so that after BF is pretreated with Si69, the S element is attached to BF, increasing the overall S element content.

[0153] Comparing the XPS results of 6BSF 5phr Si69 and untreated BSF6, it can be seen that after adding Si69, the Si-O element ratio of BSF6 increased from 10.02:33.57 to 12.33:24.76, and the S element appeared with a content ratio of 2.67%; this is because the ester group of Si69 is hydrolyzed to generate a compound with hydroxyl groups at both ends, one of which is bonded to the -OH on the BF surface, thereby increasing the Si content of the overall pretreated BSF, and the S element is also attached to the BSF surface.

[0154] From the analysis of Table 8 and Table 9, it can be seen that compared with 9BSF 3phr KH560, the Si-O element ratio of BSF9 before treatment increased from 6.6:31.25 to 3.6:12.86, and the element ratio increased by 15.91%. The analysis is because after the treatment with KH560, Si-O-Si bonds appeared. From the analysis of Figure 6, Table 8 and Table 9, it can be seen that after the treatment with different silane coupling agents, Si-O peaks representing two different elements and new peaks appeared in the XPS spectrum, indicating that after the BSF surface was modified by the silane coupling agent, the Si element on the surface and the Si element in the coupling agent formed new Si-O-Si bonds through chemical reaction.

[0155] The Si-O element ratio of sodium stearate is 4.28:19.49, and the Na element ratio is 3.06, which proves that Na ions are attached. After adding sodium stearate, the C atom content of BSF9 increased relatively compared with that of BSF9 not treated with sodium stearate. The content of Si atoms: C atoms: O atoms changed from the original 6.6:61.17:31.25 to 4.28:72.64:19.49, and the C atom content increased by 18.7%; due to the introduction of C after adding sodium stearate to pretreat BSF 17 H 35 — hydrophobic groups, the content of C atoms increased relatively, and the content ratio of Si atoms: O atoms remained almost unchanged, proving that no new Si element was introduced.

[0156] Comprehensive comparison shows that the tensile strength and other comprehensive properties of BSF9 treated with sodium stearate are higher than those of untreated BF9, and the comprehensive performance of BSF9 treated with KH550, KH560 and Si69 is the highest. The analysis shows that the sodium stearate solution can more effectively re-modify BF and enhance the compatibility between the rubber matrix and BSF.

[0157] [Energy spectrum test of basalt fiber before and after treatment]

[0158] Figure 7 is the energy spectrum of basalt fiber before and after modification by KH560.

[0159] From the analysis of Figure 7, it can be seen that the peak value of silicon (Si) element produced after adding KH560 is greater than that before treatment. The silicon (Si) element content is 32.585% before KH560 modification and 39.795% after treatment; the oxygen (O) element content is 19.136% before KH560 modification and 13.580% after treatment; This proves that new Si-O bonds are generated on the surface of the short fibers, and a dehydration condensation reaction occurs, the proportion of oxygen elements decreases, and the proportion of silicon (Si) elements increases.

[0160] The EDS results show that KH560 does adhere to the surface of the short fibers. From the perspective of a single fiber, both the BF treated with KH550 alone and the fiber treated with KH560 and KH550 have approximately circular coupling agent protrusions attached to their surfaces. However, the fiber treated with KH560 and KH550 has more coupling agents attached to its surface, and has stronger adhesion to the contact surface with the rubber.

[0161] [Analysis of surface tension test results of different adhesives]

[0162] The surface tensions of the four adhesives are shown in Table 10 and Figure 8.

[0163] Table 10 Surface tension of different adhesives

[0164]

[0165] As shown in Table 10 and Figure 8, the surface tensions of the four adhesive formulations vary greatly. Since the sodium stearate solution is solid at room temperature, it should be kept at a relatively high temperature. Among them, sodium stearate (at 60°C) is the largest and Si69 is the smallest. This reflects the surface energy of the pretreated BSF. When the same coupling agent is used to treat BSF excessively, the terminal functional groups between the molecules in the coupling agent are bonded, and the coupling agent molecular layer is too thick, which will affect the overall strength of the pretreated BSF and thus affect the compatibility between BF and the rubber matrix. Therefore, for the performance of KH550, it is necessary to qualitatively analyze its performance using physical and mechanical properties, so as to comprehensively compare the wettability of the four treatment agents. For basalt fiber, its surface energy is 60.37mN / m. When the surface tension of the adhesive is lower than the surface energy of the basalt fiber, the adhesive can better infiltrate the basalt fiber. The smaller the surface tension, the better the treatment effect of the adhesive on the BSF surface. This experiment uses BSF treated with KH550 in the drawing process. Similarly, the smaller the surface tension, the better. In summary, sodium stearate has the best uniform coating property for BF in this experiment.

[0166] [Analysis of infrared spectrum test results of different adhesive formulations]

[0167] The FTIR spectra of the powders after BF treatment with different adhesives in orthogonal test groups 1-13 were obtained using Fourier transform infrared spectrometer, and the results are shown in Figure 9. There are many groups, which are divided into groups (a) and (b).

[0168] From Figure 9, we can see that 1635cm -1 It is the absorption peak of antisymmetric COO. The BSF9 modified by sodium stearate is significantly lower than that of sodium stearate. Carbon chains are introduced into BSF, and the trough is wider, which proves that it has physical or chemical effects with water molecules on the surface of BSF, and its absorption peak is significantly reduced; but compared with untreated BSF9, its absorption peak is significantly increased, which proves that COO is introduced into BSF. It reacts with water molecules at 3433cm -1 The absorption peak of HO is significantly reduced. This is because the adhesive sodium stearate bonds with the HO on BF, making BSF hydrophobic. Compared with the peaks of untreated BSF6mm and BF9mm, the trough is wider, proving that its hydrophobicity is enhanced. -1 The corresponding peak is the C=O stretching vibration peak, which is significantly lower in intensity than that of sodium stearate, but significantly higher in absorption peak than that of untreated BSF.

[0169] BF spectrum after modification 2874.00cm -1 and 2998cm -1 The two peaks appearing are one of the most obvious changes compared to the spectrum before modification. -1 It is methyl-CH 3 The characteristic absorption peak of the symmetric stretching vibration of the CH bond is 2998cm -1 It is the characteristic absorption peak of the asymmetric stretching vibration of the C-H bond, which fully demonstrates that the modified BSF undergoes chemical adsorption with the carbon chain and introduces hydrophobic groups. Among them, the corresponding absorption peak of BF treated with sodium stearate is reduced, 2874.00cm -1 and 2998cm -1 The peaks appearing at two locations show that sodium stearate-modified BSF has the best hydrophobicity, with the sharpest absorption peak appearing there, proving that -C 17 H 35 Introduced into the polymer, methyl-CH 3 and C-H bonds are introduced into BSF.

[0170] At 2998cm -1 The second asymmetric stretching peak at is due to the -CH 2This is caused by the reaction of sodium stearate with the hydroxyl group on BF or the coupling agent. The organic end of sodium stearate is attached to the rubber matrix, the inorganic end is combined with the inorganic end of BF or KH550 attached to BF, and part of the organic end is combined with the organic end of KH550 attached to BF. 2 The amount is relatively large compared to other coupling agents, and it constitutes a larger absorption spectrum. Similarly, the treatment of KH560 is consistent with that of sodium stearate, and the group of -CH 2 The absorption peak is also larger than that of BSF6mm (not KH560).

[0171] At 3433cm -1 The third peak at 1635 cm is due to the presence of hydroxyl groups in the mixture. Compared with sodium stearate powder, the corresponding absorption peak of BF treated with sodium stearate is reduced, proving that its hydrophobicity is enhanced. -1 The first new peak at 1635cm is the characteristic of ester group (COO-). Due to the hygroscopicity of the powder, water molecules generally exist on the BSF powder in the form of capillary water. Due to the deliquescence of the BSF powder surface, water is likely to appear on the surface and react chemically with sodium stearate to form COO-. After the chemical reaction, new carboxylate groups are generated, which can be seen from the 1635cm -1 The band at proves that it constitutes a larger absorption spectrum compared to the untreated BF9mm.

[0172] At 1070-1100cm -1 The width of the left and right antisymmetric Si-O stretching vibration peaks becomes wider after adding the coupling agent. It is inferred that the chemical bonds produced by the hydrolysis of silane coupling agents KH560, KH550, and Si69 have been grafted onto the BF particles to obtain the modified BSF.

[0173] As another preferred embodiment of the present invention, this embodiment uses a latex method and pre-treated BF to work together with carbon black to achieve improved performance in the short fiber direction.

[0174] Furthermore, the short fiber reinforced rubber compound after calendering the rubber compound on the open mixing mill was put into an extruder (with a split-flow guided short fiber directional orientation die (publication number (authorization) CN113752594B)) for extrusion experiment to determine the radial performance of the rubber compound after extrusion by the short fiber directional orientation extruder head.

[0175] Furthermore, the experimental conditions of the extruder head structural parameters are as follows: the diameter of the middle flow channel section is 48 mm, the length of the middle flow channel section is 0 mm, the barrel temperature is 80 degrees, and the screw speed is 35 r / min. The extruded rubber material is cooled for 8 hours before the vulcanization test is carried out.

[0176] As another preferred embodiment of the present invention,

[0177] The specific preparation method of the rubber materials of implementation mode 1#-8# is as follows:

[0178] (1) The following is the preparation method of the rubber compound of embodiment 1# to the rubber compound of embodiment 2# (BSF9, BSF9 / KH560):

[0179] Weigh the raw materials in proportion and add them into the internal mixer in sequence for mixing;

[0180] 1) Mixing in one stage: lift the top bolt, put the raw rubber (85 parts NR, 15 parts BR) cut into small pieces into the internal mixer from the feeding port, close the top bolt, adjust the rotor speed to 70r / min, and mix for 30s;

[0181] Lift the top plug, add 5 parts of white carbon black, 21.5 parts of carbon black N234, 0.5 parts of Si 69, and 3 parts of BSF, close the top plug, mix for 120 seconds, and the rotor speed is 70r / min;

[0182] Lift the top plug, add 4 parts of zinc oxide, 2 parts of stearic acid SA, 1 part of microcrystalline wax, 21.5 parts of carbon black, 1 part of antioxidant RD, and 2 parts of 4020, close the top plug, adjust the rotor speed to 40r / min, mix for 4min30s, and discharge the glue;

[0183] 2) Second stage mixing: add 1 part of sulfur, 1.8phr DZ, and 0.3phr CTP to the masterbatch obtained in step 1); mix for 1 minute and discharge the glue.

[0184] (2) The following is the preparation method of rubber compound 3# to rubber compound 8#, wherein except for rubber compound 6# of implementation mode which is a dry process without adding BSF and rubber compound 7# which is a dry process with BSF treated with sodium stearate, the rest are wet mixing methods.

[0185] The specific steps of wet mixing of the rubber material of embodiment 3#, the rubber material of embodiment 5#, and the rubber material of embodiment 8# before adding them into the internal mixer are as follows:

[0186] Embodiment 3# (BSF9 / KH560 / latex) rubber material: 1) First, the natural latex is subjected to a wall-breaking treatment, and 850 g of natural latex (60%) solution is stirred in a high-speed stirrer at 1800 r / min for 8 min;

[0187] 2) Take silane coupling agent KH-560, 1.5wt%, 40ml, add it to 850g natural latex (60%) solution, and stir it in a high-speed stirrer at 1800r / min for 1min.

[0188] 3) Wash 3phr BSF (treated with KH550) with deionized water, add BSF to the treated natural rubber latex after the water is clear, stir at 1800r / min for 1min at room temperature, pour into a glass dish, dry in an oven for 6h; cut into small pieces; prepare NR masterbatch.

[0189] Further, embodiment 4# (BSF9 / latex) rubber material:

[0190] 1) First, the natural rubber latex was subjected to a wall-breaking treatment, and 850 g of natural rubber latex (60%) solution was stirred in a high-speed stirrer at 1800 r / min for 8 min;

[0191] 2) First, dissolve an appropriate amount of ethanol with a small amount of water, then add appropriate amounts of different coupling agents KH550, KH560 and Si69, stir until the coupling agent is fully dissolved, and then add appropriate amount of water to make the concentration of ethanol and coupling agent reach 1.5% respectively.

[0192] Wash 3phr BSF (treated with KH550) with deionized water, and put it into 40ml 1.5wt% KH560 solution after the water is clear. Stir for 1h (or 2h at 375r / min) in a high-speed rotating machine at 60℃ in a water bath to make the coupling agent adhere to the fiber surface. Take it out and dry it in an oven for 4h.

[0193] 3) Take out the dried BSF, add the BSF to the treated natural rubber latex, stir at 1800r / min for 1min at room temperature, pour into a glass dish, dry in an oven for 6h; cut into small pieces; prepare NR masterbatch.

[0194] Further, embodiment 5# (BSF9 / latex / carbon black) rubber material:

[0195] 1) First, the natural rubber latex was subjected to a wall-breaking treatment, and 850 g of natural rubber latex (60%) solution was stirred in a high-speed stirrer at 1800 r / min for 8 min;

[0196] 2) Take silane coupling agent KH560, 1.5wt%, 40ml, add it to 850g natural latex (60%) solution, and stir it in a high-speed stirrer at 1800r / min for 1min;

[0197] Wash an appropriate amount of BSF (treated with KH550) with deionized water. After the water is clear, add 3phr BSF into the treated natural rubber latex and stir at 1800r / min for 1min at room temperature.

[0198] 3) Weigh 258 g of carbon black (N234) into a beaker, then pour in 800 g of deionized water, and stir the carbon black aqueous solution in a stirrer at a speed of 750 r / min for 5 min to fully dissolve the carbon black.

[0199] 4) Then pour the latex into the carbon black aqueous solution (stirring while pouring), the stirring speed is 750r / min, and the stirring time is 1min. After completion, pour it into a glass dish, dry it in an oven for 6h, and then pour it into a large tray and spread it flat to dry to prepare the NR / BSF masterbatch.

[0200] The rubber materials #3 to #5 of implementation mode are subsequently mixed with other small materials in an internal mixer, vulcanized and formed, and the performance is tested.

[0201] It should be noted that when preparing 3#-5# rubber mixes, when BSF is added to the treated natural latex, the basalt fiber is evenly spread in the experimental dish where the latex is placed, so that the basalt is more evenly distributed in the experimental dish after breaking the latex.

[0202] When preparing the rubber compound of embodiment 5#, the basalt fiber can be evenly spread in the experimental dish where the latex is placed, and finally the carbon black aqueous solution is evenly poured in the experimental dish where the latex is placed. In this group of experiments, the method of evenly pouring the latex solution in the experimental dish where the carbon black aqueous solution is placed is adopted:

[0203] In step 3) of implementation method 5#, a beaker or flat plate with a large horizontal surface area is used. When pouring the latex into the carbon black aqueous solution, it is necessary to pour it evenly so that the short fibers inside are evenly dispersed in the superimposed solution of carbon black and latex. Finally, stir at a low speed with an agitator at a speed of 750r / min, and move the experimental plate to evenly disperse the carbon black and reduce the phenomenon of excessive flocculation, as shown in Figures 4-5.

[0204] Further, embodiment 7# (sodium stearate / BSF9) rubber material:

[0205] Same as orthogonal experiment 13, taking 18 parts of BSF as an example, the preparation method of the rubber compound is:

[0206] 1) C 17 H 35 COONa was placed in a 1:1 solution of anhydrous ethanol and water and stirred for 10 minutes to promote hydrolysis at 60°C and a stirring speed of 200 r / min.

[0207] 108 g BSF (18 parts) was soaked in 240 ml 1.5 wt% C 17 H 35 The COONa solution was heated in a constant temperature water bath for 1 h at 60 °C and a stirrer speed of 750 r / min.

[0208] Finally, the coupling agent-modified BSF was dried in an electric heated air drier at 80° C. for 4 h to obtain modified BSF.

[0209] 2) The mixing step is different from Embodiment 1# to Embodiment 2# in that BSF is replaced with BSF treated with sodium stearate solution.

[0210] Further, in the embodiment 8# (sodium stearate / latex / carbon black) rubber compound, taking 18 parts of BSF as an example, the preparation method of the rubber compound is:

[0211] 1) First, the natural rubber latex was subjected to a wall-breaking treatment, and 850 g of natural rubber latex (60%) solution was stirred in a high-speed stirrer at 1800 r / min for 8 min;

[0212] 2) C 17 H 35 COONa was placed in a 1:1 solution of anhydrous ethanol and water and stirred for 10 minutes to promote hydrolysis at 80°C and a stirring speed of 200 r / min.

[0213] 108 g BSF (18 parts) was soaked in 240 ml 1.5 wt% C 17 H 35 The COONa solution was heated in a constant temperature water bath at 60°C for 1 h and stirred at 750 r / min for 1 h.

[0214] Finally, the coupling agent-modified BSF was dried in an electric heated air drier at 80° C. for 4 h to obtain modified BSF.

[0215] 3) Take out 3 parts of BSF after drying, add BSF to the treated natural rubber latex, and stir at 1800r / min for 1 minute at room temperature.

[0216] 4) Weigh 258 g of carbon black (N234) into a beaker, then pour in 800 g of deionized water, and stir the carbon black aqueous solution in a stirrer at a stirring speed of 750 r / min for 5 min to fully dissolve the carbon black.

[0217] 5) Then pour the latex into the carbon black aqueous solution (stirring while pouring), the stirring speed is 750r / min, and the stirring time is 1min. After completion, pour it into a glass dish, dry it in an oven for 6h, pour it into a large tray, spread it flat and dry it, cut it into small pieces, and prepare it into NR / BSF masterbatch.

[0218] 6) The mixing step is different from the rubber materials of Embodiment 1# to Embodiment 2# in that the BSF is replaced with BSF treated with sodium stearate solution.

[0219] The process flow of the rubber materials of implementation mode 3# to implementation mode 8# after being added into the internal mixer is the same as that of the rubber materials of implementation mode 1# to implementation mode 2#.

[0220] Table 11 Comparison of experimental vulcanized rubber extrusion properties

[0221]

[0222] In Table 11: 1 —100% tensile stress, MPa; σ 2 —Tensile strength, MPa; τt—Tear strength, KN / m; △V—DIN volume wear volume, mm 3 ; εt—elongation at break, %; all BSF lengths are 9 mm.

[0223] 1# Rubber Material (BSF9): BSF9, treated with KH550 only during the wire drawing process;

[0224] 2# rubber compound (BSF9 / KH560): BSF9, treated again by KH560;

[0225] 3# Rubber Material (BSF9 / KH560 / latex): NR is replaced by a mixture of NR latex and latex with KH560 short fibers after drying;

[0226] 4# rubber compound (BSF9 / latex): NR is replaced by a mixture of NR latex and short fibers without KH560 added to the latex after drying;

[0227] 5# rubber compound (BSF9 / latex / carbon black): raw rubber NR is replaced by NR latex and KH560 is added to latex, then carbon black is added and dried

[0228] The mixture after

[0229] 6# rubber compound (without BSF9): no short fiber is added, other methods are the same as 1# rubber compound.

[0230] 7# Rubber (Sodium Stearate / BSF9): The difference from 1#-2# is that BSF is replaced with BSF treated with sodium stearate solution;

[0231] 8# rubber compound (sodium stearate / latex / carbon black): The difference from 5# is that the BSF is replaced with BSF treated with sodium stearate solution;

[0232] [Analysis of Example Results]:

[0233] From the analysis in Table 11, it can be seen that: 1) After extrusion, the tensile strength and elongation at break of the wet-mixed rubber (5# rubber) increased by 2.21Mpa (increased by 10.74%) and decreased by 0.77% respectively compared with the traditional mixed rubber (2# rubber, dry method / BSF9 / KH560), and the DIN wear loss decreased by 13.3%. This shows that the wet-mixed rubber has good mechanical and physical properties. After extrusion, the tensile strength of 8# rubber (latex / carbon black / sodium stearate treated BSF) increased by 6.2% compared with 7# rubber (dry method / BSF9 / sodium stearate), and the DIN wear performance increased by 6.3%. Before / after extrusion, the tensile strength of 7# rubber increased by 8.9% / 5.1% compared with 2# rubber, and the DIN wear loss decreased by 9.6% / 8.86%.

[0234] Compared with the rubber compound without basalt short fiber (BSF) (6# rubber), the hardness of the rubber sample increases with the addition of BSF. This is mainly because the basalt short fiber dispersed in the rubber plays a role in strengthening the skeleton, improving the rigidity of the rubber and increasing the hardness of the rubber.

[0235] After extrusion, compared with BSF9mm (1# rubber without KH560), BSF9mm (2# rubber with KH560) has a 4.20% increase in tensile strength and a 11.85% increase in DIN abrasion performance. At the same time, the addition of KH560 is beneficial to improving the lubrication and flexibility of the rubber molecular chain, improving the fluidity of the rubber, and the various physical and mechanical properties are higher than those without KH560. After extrusion, the DIN abrasion of 2# rubber (BSF9mm dry method with KH560) is relatively reduced by 5.15% compared with 6# rubber (without short fibers), but the tensile strength after extrusion is not increased, and the elongation at break is high. Analysis shows that there is no filler when short fibers are not added; and after the short fibers in the rubber compound in the tensile specimen are cut off, the strength at the tensile section is lower than the tensile specimen strength of the rubber compound without short fibers.

[0236] 2) After extrusion, compared with the rubber compound without BSF (6# rubber), the tensile strength of BSF9mm (7# rubber, sodium stearate added by dry method) increased by 2.61%, and the DIN wear performance increased by 13.56%. The tensile strength was not much different, but the DIN wear performance was significantly improved. This is because after extrusion, the radial orientation degree of the short fibers in the SFRC reinforced with sodium stearate increased significantly, and a strong bonding surface was formed between sodium stearate and the rubber matrix. BSF played a good reinforcing role, and the fibers could be well reinforced in the vertical direction during wear, thereby greatly improving the overall comprehensive performance.

[0237] After extrusion, the tanδ values ​​of #7 rubber (latex carbon black KH560) and #4 rubber (dry process adding KH560) at 0℃ were 0.142294 / 0.159801 respectively; at 60℃, the tanδ values ​​of #7 rubber (latex carbon black KH560) and #4 rubber (dry process adding KH560) were 0.0999589 / 0.125668 respectively. The rolling resistance of #7 rubber (latex carbon black KH560) was 20.46% lower than that of #4 rubber (dry process adding KH560).

[0238] After extrusion, at 60°C, the rolling resistance performance of #5 rubber (BSF9mm, latex plus KH560) / 0.10587 is improved by 22.61% compared with BSF9mm (without KH560) / 0.136803.

[0239] After extrusion, the tanδ value at 0℃, the radial anti-slip performance of #9 rubber (dry method, sodium stearate) extrusion, tanδ value is 0.161143, and the radial anti-slip performance of extrusion without adding BSF (#8 rubber), tanδ value is 0.15325, and the anti-slip performance is improved by 5.15%. The tanδ value at 60℃, the rolling resistance value of sodium stearate / no BSF added during extrusion are 0.110295 / 0.11731, respectively, and the rolling resistance performance is improved by 5.98%. The anti-slip performance of #4 rubber (BSF9 dry method plus KH560) is 4.27% higher than that of no BSF (#8 rubber).

[0240] After extrusion, the tanδ value at 60°C, #7 rubber (latex / carbon black / KH560) / 0.0999589 is 5.58% higher in rolling resistance than #5 rubber (BSF9 / KH560 / latex) / 0.10587.

[0241] The interfacial interaction between wet-mixed BSF and the rubber matrix becomes stronger and limits the movement of rubber molecular chains, increasing the elastic modulus of the composite material; BSF is fully dispersed in the latex matrix before entering the internal mixer. Compared with internal mixer mixing, the dispersion of wet-mixed BSF is relatively more uniform.

[0242] Due to the unique rigidity of BSF, the rubber fiber is oriented radially. With the addition of KH560, a KH560 Si-O bonding layer is uniformly generated on the surface of BSF based on the original KH550, which expands the contact area between BSF and the rubber matrix, limits the deformation of the rubber matrix, improves the interface interaction, and its rolling resistance is relatively reduced. The loss factor is small at 0℃ and 60℃. When external force is applied, the rubber matrix is ​​transferred to the BSF through the interface phase, and the loss factor tanδ indirectly reflects the interface effect between the rubber matrix and BSF. Generally speaking, the larger the tanδ peak value, the worse the interface effect between BSF and rubber.

[0243] In wet mixing, the temperature corresponding to the tanδ peak, i.e., the glass transition temperature, also decreases. This may be due to the low glass transition temperature of wet mixing. When the glass transition temperature of the rubber is reached, BSF can still play a reinforcing effect in the rubber matrix, and will not cause brittle failure of the rubber at low temperatures compared to dry mixing. Generally, the maximum value of tanδ decreases with the increase of filler dosage. The smaller the tanδ, the stronger the interaction between BSF / rubber, the more restricted the activity of the rubber molecular segments, the larger the storage modulus G′, resulting in lower loss of the vulcanized rubber and a lower tanδ peak. Adding BSF in the orientation direction can improve the rolling resistance of the composite material.

[0244] The above embodiments are only used to illustrate and not to limit the technical solutions of the present invention. Any modification or partial replacement that does not deviate from the spirit of the present invention should be included in the scope of the claims of the present invention.

Claims

1. A method for preparing a basalt short fiber oriented reinforced rubber composite material, characterized in that: The following steps are involved: (1) Pretreatment of basalt staple fibers; (2) weighing the pretreated short fibers and other raw materials in a certain proportion, and sequentially adding them into an internal mixer for mixing; (3) After the mixing is uniform, the sheet is produced, and the obtained rubber material is calendered and oriented along the direction of the short fibers, vulcanized, and left for 6 hours for use; The raw material composition of the basalt short fiber oriented reinforced rubber composite material is calculated by weight: NR (SCR5) 85 parts; TMQ (RD) 1 part; BR 15 parts; anti-scorch agent CTP 0.3 parts; white carbon black 5 parts; microcrystalline wax 1 part; ZnO 4 parts; Si69 0.5 parts; stearic acid 2 parts; antioxidant 4020 2 parts; carbon black N234 43 parts; DZ 1.8; pre-treated basalt short fiber 3 parts; S total 1 portion.

2. The method for preparing a basalt short fiber oriented reinforced rubber composite material according to claim 1, characterized in that: The pretreatment step of first treating the basalt staple fibers comprises: (1) First, dissolve an appropriate amount of ethanol in a small amount of water, then add appropriate amounts of different coupling agents KH550, KH560 and Si69, stir until the coupling agent is fully dissolved, and then add appropriate amounts of water to make the concentrations of ethanol and coupling agent reach 1.5% respectively; (2) The pre-treated basalt short fibers were immersed in the prepared 1.5 wt% coupling agent solution for 1 hour. During the immersion process, the stirrer speed was increased for dispersion for 1 hour. After being taken out, they were placed in a drying oven at 80° C. for 4 hours to accelerate the reaction between the coupling agent and the surface chemical components of the basalt short fibers, thereby obtaining pre-treated basalt fibers.

3. The method for preparing a basalt short fiber oriented reinforced rubber composite material according to claim 2, characterized in that: The pretreatment method for treating the basalt short fibers first specifically includes the following steps: (1) At 60°C, 1.5 g of coupling agent was added to 62 ml of anhydrous ethanol and 49 ml of deionized water and stirred for 10 minutes for hydrolysis. The stirring speed was 200 r / min, and 111 ml of 1.5 wt% coupling agent solution with a total mass of 100 g was prepared; (2) The 3phr / 4phr / 5phr chopped basalt fibers after the original basalt short fibers were treated were cleaned with deionized water and placed in a beaker, and then immersed in 40ml / 54ml / 67ml of 1.5% by mass KH550 or KH560 or Si69 solution, respectively, and stirred for 1 hour at a speed of 750r / min and a temperature of 60°C using a high-speed rotary machine, and then placed in an electric blower dryer for drying at 80°C for 4 hours.

4. The method for preparing a basalt short fiber oriented reinforced rubber composite material according to claim 1, characterized in that: The pretreatment method of first treating basalt short fibers also includes a sodium stearate solution pretreatment method, the steps of which are: (1) Add appropriate amount of C 17 H 35 COONa powder is placed in a solution with a quantitative mass fraction ratio of anhydrous ethanol to water = 1:1, and stirred until the coupling agent is fully dissolved; (2) Soak an appropriate amount of pre-treated basalt short fibers in the above 1.5 wt% C 17 H 35 The solution of COONa was stirred and heated at a stirring speed of 1 h, and then taken out and placed in a drying oven at 80°C for 4 h to obtain pretreated basalt fibers.

5. The method for preparing a basalt short fiber oriented reinforced rubber composite material according to claim 4, characterized in that: The sodium stearate solution pretreatment method specifically comprises the following steps: (1) 15 g C 17 H 35 COONa powder was placed in 985 g of a solution with a mass fraction ratio of anhydrous ethanol to water = 1:1, and stirred for 10 minutes to promote hydrolysis at 60°C and a stirring speed of 200 r / min; (2) 108 g of the pre-treated basalt short fibers were soaked in 240 ml of the above 1.5 wt% C 17 H 35 In the COONa solution, the constant temperature of the water bath is 60°C, and the stirrer speed is 750r / min for stirring and heating for 1h.

6. The method for preparing a basalt short fiber oriented reinforced rubber composite material according to claim 1, characterized in that: The internal mixer mixing process in step (2) of the preparation method of the basalt short fiber oriented reinforced rubber composite material is: 1) Mixing in one stage: lift the top bolt, put 85 parts of NR and 15 parts of BR cut into small pieces into the internal mixer from the feeding port, close the top bolt, adjust the rotor speed to 70r / min, and mix for 30s; Lift the top bolt, add 5 parts of white carbon black, 21.5 parts of carbon black N234, 0.5 parts of Si 69, and 3 parts of basalt short fibers, close the top bolt, mix for 120 seconds, and the rotor speed is 70r / min; Lift the top plug, add 4 parts of zinc oxide, 2 parts of stearic acid SA, 1 part of microcrystalline wax, 21.5 parts of carbon black, 1 part of antioxidant RD, and 2 parts of 4020, close the top plug, adjust the rotor speed to 40r / min, mix for 4min30s, and discharge the glue; 2) Second stage mixing: The masterbatch obtained in step 1) was added with 1 part of sulfur, 1.8 phr DZ and 0.3 phr CTP; mixed for 60 seconds and discharged.

7. The method for preparing a basalt short fiber oriented reinforced rubber composite material according to claim 1, characterized in that: In the calendering process of the open mill, the roller temperature is 40-50° C., the roller distance of the open mill is adjusted to 1 mm, and the roll is rolled 5 times along the calendering direction of the open mill; then the roller distance is adjusted to 3 mm, and the roll is rolled 5 times along the calendering direction to obtain a basalt short fiber composite material oriented along the calendering direction.

8. The method for preparing a basalt short fiber oriented reinforced rubber composite material according to claim 1, characterized in that: The first treatment method of the basalt fiber is KH550 first treatment, and the pretreatment method is sodium stearate solution treatment.

9. The method for preparing a basalt short fiber oriented reinforced rubber composite material according to claim 1, characterized in that: The pretreatment method comprises co-treating the pre-treated basalt short fibers with a sodium stearate solution, latex and carbon black; The method for co-processing basalt short fibers with sodium stearate solution, latex and carbon black specifically comprises the following steps: 1) First, the natural rubber latex was subjected to a wall-breaking treatment, and 850 g of the natural rubber latex solution was stirred in a high-speed stirrer at 1800 r / min for 8 min; 2) C 17 H 35 COONa powder was placed in anhydrous ethanol: water = 1:1 solution and stirred for 10 minutes to promote hydrolysis at 80°C and 200 r / min stirring speed; 108g of pre-treated basalt short fibers were soaked in 240ml of 1.5wt% C 17 H 35 The COONa solution was heated in a constant temperature water bath at 60°C for 1 h and stirred at 750 r / min for 1 h. Finally, the basalt staple fibers modified by the sodium stearate solution were dried in an electric heating blast dryer at 80°C for 4 h to obtain modified basalt staple fibers; 3) Take out 3 portions of dried basalt short fibers, add the basalt short fibers into the treated natural rubber latex, and stir at 1800 r / min for 1 min at room temperature; 4) Weigh 258g N234 into a beaker, then pour in 800g deionized water, stir the carbon black aqueous solution in a stirrer at a stirring speed of 750r / min for 5min to fully dissolve the carbon black; 5) Then pour the latex into the carbon black aqueous solution while stirring at a stirring speed of 750r / min for 1min. After completion, pour it into a glass dish, dry it in an oven for 6h, pour it into a large tray, lay it flat and dry it, cut it into small pieces, and prepare it into NR / BSF masterbatch; The mixing step of the rubber material after the method of co-treatment of the basalt short fibers with the sodium stearate / KH560 solution, latex and carbon black is the same as the internal mixer mixing process described in claim 6, the difference being that 85 parts of NR in the raw rubber cut into small pieces are replaced with NRB / SF masterbatch, and the pre-treated basalt short fibers are not added separately.

Citation Information

Patent Citations

  • Fiber / metal layer structure composite and preparation method thereof

    CN106553397A

  • High-performance conductive rubber composite material and preparation method thereof

    CN106810878A

  • Equipment and method for manufacturing sheet-like short fiber radially oriented reinforced rubber composite materials

    CN113752594B

Cited By

  • Nitrile rubber and ethylene propylene diene monomer blending material as well as preparation method and application thereof

    CN121914468A

  • A nitrile rubber and ethylene propylene diene rubber blended material, a preparation method and application thereof

    CN121914468B